ESTROGEN RECEPTOR POSITIVE TUMORS: DO REPRODUCTIVE FACTORS EXPLAIN DIFFERENCES IN INCIDENCE BETWEEN BLACK AND WHITE WOMEN? - Warner, Erica T. (2013)
PURPOSE: The incidence of estrogen receptor positive (ER+) breast cancer is higher among white women relative to black women. In two large prospective cohorts, the Black Women’s Health Study (BWHS) and the Nurses’ Health Study II (NHSII), we investigated whether reproductive factors explain the difference. METHODS: During 1,582,083 person-years of follow-up of 140,914 women observed from 1995-2007, 327 ER+ breast cancers were identified among black women in BWHS and NHSII and 1179 among white women in NHSII. Cox proportional hazards regression models, stratified by race and pooled, were used to estimate hazard ratios (HR) and 95% confidence intervals (CI) for the association of race, parity, age at first birth, and lactation in relation to risk of ER+ cancer with adjustment for age and other breast cancer risk factors. RESULTS: Age at first birth differed markedly in the two groups, with 66% of parous black women having their first child before age 25 as compared with 36% of white women. Each additional year of age at first birth was associated with a 4% increased risk of ER+ breast cancer among both racial groups. Relative to nulliparous women, parous women were at decreased risk of ER+ breast cancer (HR 0.59, 95% CI: 0.20, 1.77), in black women and (HR 0.63, 95% CI: 0.45, 0.87) in white women. The HR for the association of black race with ER+ cancer was 0.67 (95% CI: 0.53, 0.84) in a model that adjusted for age only, 0.77 (95% CI: 0.61, 0.99) in a model that controlled for parity, age at first birth, and other reproductive/hormonal factors, and 0.83 (95% CI: 0.70, 0.98) in a model that additionally controlled for other breast cancer risk factors such as alcohol consumption and use of hormone supplements. Similar associations were seen among premenopausal women and in an analysis restricted to ER+PR+ tumors. CONCLUSIONS: Reproductive factors explained some of the higher incidence of ER+ tumors among white women as compared to black women.